Potential of Latent Heat Load Removal by Activated Carbons for Energy Savings of Air Conditioning Systems. Issue 1 (March 2021) - Miyazaki, T; Chairunnisa,; Miksik, F.; Thu, K; Miyawaki, J; Nakabayashi, K; Wijayanta, A T; Rahmawati, F; Kristiawan, B; Yaningsih, I
Abstract: The study aims to achieve energy savings of air conditioning systems using desiccant dehumidification with low-cost adsorbent. For this purpose, two existing activated carbons were evaluated in terms of water adsorption capacity. The theoretical calculation of effective adsorption from the water adsorption isotherms revealed that the studied activated carbons have promising potential in dehumidification application. In addition to that, the improvement of cooling COP of air conditioners was predicted by simulation of heat pump cycle. The results showed that the COP improved by 50%, which was equivalent to the reduction of electricity input by 30%, with the raise of evaporation temperature from 8.5°C to 18.5°C. The results encouraged the separation of dehumidification load from air conditioners to achieve large energy savings.